Replanning of an intensive therapy unit. Issue 6355 (4th December 1982) - Ryan, D W; Copeland, P F; Miller, J; Freeman, R
Abstract : Considerable effort is needed when replanning an intensive therapy unit to avoid repeating mistakes in design, such as lack of windows and an impractical working area. Early consultation with the nursing and medical staff primarily responsible for such a unit is essential. The considerable technological innovations in intensive care will require flexibility in the future if they are to be incorporated into existing facilities.